(untitled) (Experimental biology, 2016)
The analysis of morphological and osteological characteristics eyed shad Alosa Saposhnikovi, (Grimm, 1887), the western part of the Middle Caspian counting on 6 and 33 plastic characteristics. Some features of ecology, morphology, nutrition Dagestan coast of the Caspian Sea. It established the total average number of vertebrae eyed shad Alosa Saposhnikovi, (Grimm, 1887), the western part of the Middle Caspian in the meantime. Revealed a clear tendency to decrease, possibly due to have taken place deep hydrological and hydro-chemical changes in the Caspian Sea over the past century. The histological structure of the liver eyed shad Alosa Saposhnikovi, (Grimm, 1887) was a decrease in the number of cores in the control area, the cells acquired a rounded shape on the shell observed perinuclear clumps of chromatin, the optical cavities in the cytoplasm were absent. In females eyed shad Alosa Saposhnikovi, (Grimm, 1887) at a time when egg cells pass vitellogenesis (autumn) and during oocyte growth trophoplasmatic (spring), there are signs enhance the functional activity of the liver. Fatness females eyed shad Alosa Saposhnikovi, (Grimm, 1887) the length of 19-33 cm Fulton ranged from 1.09 to 1.52, male 17-28 cm in length - from 1.02 to 1.64, an average of 1, 34 and 1.26 respectively.